2021
DOI: 10.3389/fphar.2021.760186
|View full text |Cite
|
Sign up to set email alerts
|

Blocking HMGB1/RAGE Signaling by Berberine Alleviates A1 Astrocyte and Attenuates Sepsis-Associated Encephalopathy

Abstract: As a life-threatening multiple organ dysfunction attributable to maladjusted host immune responses to infection, sepsis is usually the common pathway to serious prognosis and death for numerous infectious diseases all over the world. Sepsis-associated encephalopathy (SAE) is frequently complicated by septic conditions, and is one of the most important reasons for increased mortality and poor outcomes in septic patients which is still an urgent clinical problem need to be solved. In this research, a conspicuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(44 reference statements)
0
14
0
Order By: Relevance
“… Blocking HMGB1/RAGE Signaling. [ 100 ] Intestine Rats; CLP Berberine improved compromised GVB. Modulating the ApoM/S1P pathway.…”
Section: Introductionmentioning
confidence: 99%
“… Blocking HMGB1/RAGE Signaling. [ 100 ] Intestine Rats; CLP Berberine improved compromised GVB. Modulating the ApoM/S1P pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia can also induce the transformation of A1 astrocytes to injury neurons [ 115 ]. In addition to secreting inflammatory cytokines [ 116 ], astrocytes also affect the release of neurotransmitters, which at last leads to neuronal injury [ 117 ]. Sepsis can dysfunction the autophagy and pyroptosis homeostasis [ 118 ] and activate ferroptosis [ 119 ] and endoplasmic reticulum stress of neurons, all of which could lead to neuronal damage [ 120 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition to alleviating the systemic inflammatory response, BBR also significantly improved DIC and MOF caused by sepsis ( Yuan et al, 2021 ), ( Shi et al, 2021 ), ( Chen et al, 2021 ). A study has indicated that BBR and the derivatives could attenuate coagulation activation, organ dysfunction and further decreased lethality in bacterial sepsis.…”
Section: Bbr Ameliorates Cs Induced By Sepsis and Viral Infectionsmentioning
confidence: 99%
“…The mechanism is that BBR blocked the caspase-11 inflammatory pathway by inhibiting the cytoplasmic translocation of LPS via blocking Msr1, a scavenger receptor that mediates endocytosis of LPS ( Yuan et al, 2021 ). In an experimental model of sepsis-associated encephalopathy (SAE), BBR targeted HMGB1/RAGE signaling to suppress the quantity of inflammatory events of cell factors and astrocyte activation in the cerebrum of SAE mice, thereby alleviating cognitive impairment caused by sepsis ( Shi et al, 2021 ) Moreover, septic cardiomyopathy (SCM) is the most common type of sepsis-related organ dysfunction. Chen et al (2021) found that BBR reduced myocardial injury in sepsis rats, by inhibiting sepsis-induced TLR4/NF-κB signal pathway activation and decreasing the expression levels of TNF-a, IL-1β and other inflammatory factors.…”
Section: Bbr Ameliorates Cs Induced By Sepsis and Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation